2020
DOI: 10.3390/molecules25051138
|View full text |Cite
|
Sign up to set email alerts
|

A Concise Approach to N-Substituted Rhodanines through a Base-Assisted One-Pot Coupling and Cyclization Process

Abstract: An efficient approach to obtain functionalized rhodanines was developed through a base-assisted one-pot coupling and continuous cyclization of a primary amine, carbon disulfide, and methyl (2-chloroacetyl)carbamate. This conversion tolerates a broad range of functional groups and can be used to scale the preparation of N-substituted rhodanines in excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…This type of compounds, when interacting with carbon disulfide 2, forms carbamine salts 3. The resulting compounds, when interacting with chloroacetic acid and their derivatives, cyclize into the target compounds [1][2][3]23 Alternative method for converting aminogroup into rhodanine cycle 5 includs the reaction of aminocompounds with acid 4. [1][2][3] Rhodanine derivatives 5 are also formed by the raction of isothiocyanates 6 with mercaptoacetic acid 7.…”
Section: Methods Of Construction Of the Rhodanine (2-thioxothiazolidi...mentioning
confidence: 99%
See 1 more Smart Citation
“…This type of compounds, when interacting with carbon disulfide 2, forms carbamine salts 3. The resulting compounds, when interacting with chloroacetic acid and their derivatives, cyclize into the target compounds [1][2][3]23 Alternative method for converting aminogroup into rhodanine cycle 5 includs the reaction of aminocompounds with acid 4. [1][2][3] Rhodanine derivatives 5 are also formed by the raction of isothiocyanates 6 with mercaptoacetic acid 7.…”
Section: Methods Of Construction Of the Rhodanine (2-thioxothiazolidi...mentioning
confidence: 99%
“…The methylene group in rhodanine derivatives 10 is highly active and, upon interaction with furfural and its substituted derivatives 11 in the presence of basic catalysis, easily forms the target (5E)-3-R 1 -5-[(5-R-furan-2-yl)methylidene]-2-sulfanylidene-1,3-thiazolidin-4-ones 12 (Scheme 3). [1][2][3][23][24][25][26] The geometric placement of substituents at the 5-th position of the rhodanine ring of the above compounds has not been studied separately. However, by analogy with other 5-arylidenerhodanines, it can be argued that this is the Z-configuration 1-3 .…”
Section: Methods Of Construction Of the Rhodanine (2-thioxothiazolidi...mentioning
confidence: 99%
“…The proposed reaction mechanism for this process is depicted in [Figure 3]. [31] In scheme 7, Kumar et al demonstrated an effective and stereospecific procedure for the conversion of free amino group (9) to the equivalent (±)-2-thioxo-thiazolidine-4ones. The synthetic strategy involves the conversion of amino acid to ammonium salt which, in turn, reacts with carbon disulfide (2) to form dithiocarbomates (10).…”
Section: Methods For the Synthesis Of Rhodanine Corementioning
confidence: 99%
“…All the other solvents were investigated, and MeCN was used as the most selective one (yield 94%, Scheme 6, Figure 3a). The proposed reaction mechanism for this process is depicted in Figure 3b (Liang et al, 2020).…”
Section: Synthesis Of Rhodanine From Carbamatementioning
confidence: 99%